Examining Word List and Processes in Law of The Republic of Indonesia Number 6 Year 2011 - Eva Tuckyta Sari Sujatna; Cece Sobarna (Ranah: Jurnal Kajian Bahasa, 2021)
This research tries to figure out the word list and the types of processes in Law of the Republic of Indonesia No 6 of Year 2011 concerning immigration. The research method applied in this research is descriptive method to describe the word list and the process in each data. Based on the result of the data analysis, firstly, it was found that the word “yang” is the highest frequency gramatically, while “pasal” is the highest frequency lexically. Secondly, it was reported there are four different processes; they are material process, mental process, relational process, and verbal process. Among the processes, the dominant process applied in Law of the Republic of Indonesia No 6 Year 2011 concerning Immigration is the verb “dipidana” as material processes, “menolak” as mental processes, “melarang” as verbal processes, and “adalah” as relational processes. AbstrakTujuan penelitian ini untuk mendeskripsikan kosakata dan jenis-jenis proses dalam Undang-Undang Republik Indonesia Nomor 6 Tahun 2011 tentang Keimigrasian. Metode penelitian yang digunakan dalam penelitian ini adalah metode deskriptif untuk mendeskripsikan kosakata dan proses dalam setiap data. Berdasarkan hasil analisis data, pertama ditemukan bahwa kata “yang” secara gramatikal memiliki frekuensi tertinggi, sedangkan secara leksikal kata “pasal” memiliki frekuensi tertinggi. Kedua, ditemukan empat proses yang berbeda, yaitu proses material, proses mental, proses relasional, dan proses verbal. Di antara proses-proses tersebut, proses yang dominan diterapkan dalam UUD RI No 6 Tahun 2011 tentang Keimigrasian adalah verba “dipidana” sebagai proses material, “menolak” sebagai proses mental, “melarang” sebagai proses verbal, dan “adalah” sebagai proses relasional.